A probabilistic framework for life-cycle cost analysis of bridge decks constructed with different reinforcement alternatives. (15th October 2021) - Shen, Ligang; Soliman, Mohamed; Ahmed, Samir A.
Highlights: Probabilistic life-cycle cost analysis for concrete bridge decks under corrosion. Agency and user cost quantification for decks with different reinforcement types. Detailed traffic delay estimation based on vehicle queuing and traffic control procedures. Analyze effect of concrete cover, bridge location, traffic volume, and number of lanes. Optimum deck reinforcement selection based on bridge attributes and life-cycle cost. Abstract: Reinforced concrete bridge decks with conventional reinforcement may experience deterioration due to deicing salts or marine environmental conditions. Routine maintenance, rehabilitation, and repair activities are implemented to maintain an acceptable performance level. In addition to the significant financial resources required to conduct these activities, traffic congestions at work zones can lead to an increase in delays and crash risk for road network users, as well as other environmental and social impacts. These user costs arising from traffic congestions can be significantly higher than the cost of maintenance, rehabilitation, and repair activities. Despite the higher initial unit cost, bridge decks constructed with corrosion resistant reinforcement can provide a longer service life and require less maintenance activities. Accordingly, from a life-cycle cost perspective, corrosion resistant reinforcement could be a better alternative compared to conventional reinforcement for bridge decks. This paper presents a probabilistic framework to estimate the life-cycle cost associated with bridge decks constructed with different reinforcement alternatives. The framework accounts for reinforcement deterioration to evaluate the maintenance activity timeline considering influential corrosion-related parameters (e.g., reinforcement type, concrete cover, and bridge location, among others). Key attributes affecting traffic delays, including traffic volume, number of lanes, and vehicular queuing, are also included in the framework. Monte Carlo simulation is used to predict the corrosion-induced cracking time, service life of the bridge deck, and the life-cycle cost under uncertainty. A bridge located in Pennsylvania is used as an illustrative example to demonstrate the application of the proposed framework. The results show that the concrete cover, chloride exposure condition, average daily traffic, and number of traffic lanes have a significant effect on the life-cycle cost of reinforced concrete bridge decks; especially for those constructed with conventional reinforcement. The presented framework can be beneficial in selecting the optimum bridge deck reinforcement type from a life-cycle cost perspective.